Advertising expenditures on child-targeted food and beverage products in two policy environments in Canada in 2016 and 2019 - Potvin Kent, Monique; Pauzé, Elise; Remedios, Lauren; Wu, David; Soares Guimaraes, Julia; Pinto, Adena; Bagnato, Mariangela; Pritchard, Meghan; L'Abbé, Mary; Mulligan, Christine; Vergeer, Laura; Weippert, Madyson (Université d'Ottawa | University of Ottawa, 2023)
Background: The food industry advertises unhealthy foods intended for children which in turn fosters poor diets. This study characterized advertising expenditures on child-targeted products in Canada and compared these expenditures between Quebec, where commercial advertising to children under 13 is restricted, and the rest of Canada, where food advertising to children is self-regulated. Methods: Advertising expenditures data for 2016 and 2019 for 57 select food categories and five media channels were licensed from Numerator. Products and brands targeted to children were identified based on their nature and the advertising techniques used to promote them. Advertising expenditures were classified as healthy/unhealthy using Health Canada’s nutrient profile model. Expenditures per child capita aged 2–12 years were calculated and expenditures from 2016 were adjusted for inflation. Advertising expenditures were described by media, food category, year, and geographic region. Results: Overall, $57.2 million CAD was spent advertising child-targeted products in Canada in 2019. Television accounted for 77% of expenditures followed by digital media (18%), and the food categories with the highest expenditures were candy/chocolate (30%) and restaurants (16%). The totality of expenditures (99.9%-100%) in both Quebec and the rest of Canada in 2016 and 2019 were considered ‘unhealthy’. Across all media channels (excluding digital), advertising expenditures were 9% lower in 2019 versus 2016. Advertising expenditures per capita were 32% lower in Quebec ($9.40/capita) compared to the rest of the country ($13.91/capita). Conclusion: In Canada, millions are spent promoting child-targeted products considered inappropriate for advertising to children. While per capita advertising expenditures for these products are lower in Quebec compared to the rest of Canada, they remain high, suggesting that Quebec’s commercial advertising restrictions directed to children are likely not sufficiently protecting them from unhealthy food advertising.
Keywords: Food; Beverages; Canada; Television; Food Industry; Policy; Advertising; Expenditures; Children; Quebec